Diagnostic potential of NETosis-derived products for disease activity, atherosclerosis and therapeutic effectiveness in Rheumatoid Arthritis patients. (August 2017) - Pérez-Sánchez, C.; Ruiz-Limón, P.; Aguirre, M.A.; Jiménez-Gómez, Y.; Arias-de la Rosa, I.; Ábalos-Aguilera, M.C.; Rodriguez-Ariza, A.; Castro-Villegas, M.C.; Ortega-Castro, R.; Segui, P.; Martinez, C.; Gonzalez-Conejero, R.; et al.
Abstract: Objectives: 1) To assess the association of NETosis and NETosis-derived products with the activity of the disease and the development of cardiovascular disease in RA; 2) To evaluate the involvement of NETosis on the effects of biologic therapies such as anti-TNF alpha (Infliximab) and anti-IL6R drugs (Tocilizumab). Methods: One hundred and six RA patients and 40 healthy donors were evaluated for the occurrence of NETosis. Carotid-intimae media thickness was analyzed as early atherosclerosis marker. Inflammatory and oxidative stress mediators were quantified in plasma and neutrophils. Two additional cohorts of 75 RA patients, treated either with Infliximab (n = 55) or Tocilizumab (n = 20) for six months, were evaluated. Results: NETosis was found increased in RA patients, beside myeloperoxidase and neutrophil elastase protein levels. Cell-free nucleosomes plasma levels were elevated, and strongly correlated with the activity of the disease and the positivity for autoantibodies, alongside inflammatory and oxidative profiles in plasma and neutrophils. Moreover, ROC analyses showed that cell-free nucleosomes levels could identify RA patients showing early atherosclerosis with high specificity. RA patients treated either with IFX or TCZ for six months exhibited decreased generation of NETs. Concomitantly, clinical parameters and serum markers of inflammation were found reduced. Mechanistic in vitro analyses showed that inhibition of NETs extrusion by either DNase, IFX or TCZ, further abridged the endothelial dysfunction and the activation of immune cells, thus influencing the global activity of the vascular system. Conclusions: NETosis-derived products may have diagnostic potential for disease activity and atherosclerosis, as well as for the assessment of therapeutic effectiveness in RA. Highlights: NETosis-derived products are linked to clinical and CVD-related markers in RA. NETs might act as biomarkers for both, disease activity and atherosclerosis. In vivo, Anti-TNFalpha and anti-IL6 drugs inhibited NETosis in RA. In vitro, inhibition of NETosis by TCZ/IFX influence vascular system activity.